(untitled) (Revista Rupturas, 2017)
This article discusses the costs associated with migratory experience. To do this, a review is made of the arguments that are often raised to highlight the benefits of migration, especially family remittances and their alleged development impact. Based on interviews with men who emigrated and returned, an analysis is made of some of the impacts that migration has on the lives of families and communities of origin. From this analysis, a romantic view is challenged that highlights only positive aspects of migration, while avoiding a review of the factors that continue to lead to migration. The article is nourished by information collected in fieldwork made from interviews with Costa Rican people who migrated and returned to Costa Rica, as well as the results of a survey applied in the framework of a broader investigation. The use of both sources of information allows the complementarity between the use of qualitative and quantitative methodology.